2012
DOI: 10.6002/ect.2011.0103
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antibodies Against Major Histocompatibility Complex Class I-Related Chain A in Long-term Renal Graft Recipients

Abstract: Objectives: To determine the prevalence, allele specificity, and intensity of anti-MICA antibodies in long-term renal graft recipients and to investigate their association with impaired renal function. Materials and Methods: Sixty-eight long-term (> 10 y) renal graft recipients were divided into 2 groups: (1) patients with impaired renal function (serum creatinine ≥ 2 mg/dL, n=6); (2) patients with normal renal function (serum creatinine < 176.8 µmol/L, n=62). Anti-MICA antibodies were tested using Luminex sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
(13 reference statements)
0
6
0
1
Order By: Relevance
“…Li et al. did not find any significant differences in MICA antibodies between patients with impaired kidney function and normal renal function over 10 yr. Further analysis showed that the level of MICA antibodies in long‐term renal graft cases were remarkably lower than in patients with normal renal function, suggesting that MICA antibodies are involved in graft rejection.…”
Section: Mica In Renal Transplantationmentioning
confidence: 92%
“…Li et al. did not find any significant differences in MICA antibodies between patients with impaired kidney function and normal renal function over 10 yr. Further analysis showed that the level of MICA antibodies in long‐term renal graft cases were remarkably lower than in patients with normal renal function, suggesting that MICA antibodies are involved in graft rejection.…”
Section: Mica In Renal Transplantationmentioning
confidence: 92%
“…According to Zou Y. et al MICA antigens are significantly associated with and might play a role in rejection, in the absence of previous sensitization against HLA, like in recipients of first transplants, patients who received grafts from well-HLA-matched donors and recipients not previously sensitized against HLA. The role of anti-HLA and anti-MICA antibodies in graft failure was confirmed in several studies [66][67][68]. However, Lemy A. at al.…”
Section: The Role Of Anti-mica Antibodies In Kidney Transplantationmentioning
confidence: 97%
“…In renal , lung , heart and liver transplantation, recent reports identified posttransplantation MICA antibody development as a risk factor for allograft rejection. In HSCT these alloantibodies are described as an independent risk factor for development of acute and chronic GVHD (graft vs host disease) .…”
Section: Introductionmentioning
confidence: 99%